The Association Between Sleep Quality and Eating Habits among International Students in South Korea. (29th May 2020) - Im, Hyo Hyeon; Doo, Hyungie; Chun, Hyejin; Suh, Eunkyung; Han, Kunhee; Wang, Chunyang; Doo, Miae
Abstract: Objectives: This study was performed to identify the relationship between sleep quality and eating habits change after going abroad for international students in South Korea. Methods: Using self-report questionnaires, data on general characteristics, health-related variables, sleep pattern and eating habits after going abroad were collected from 225 international students (105 men; 120 women). Results: More half of the international students experienced poor sleep quality [poor by PSQI (Pittsburgh Sleep Quality Index) = 52.0%]. Subjects who reported poor sleep quality had significantly higher total score of eating habits after going abroad (P-value < 0.001), the change of environment for dietary consumption ( P  = value = 0.010) and eating problems after going abroad (P-value = 0.001) than those who reporting good sleep quality. The high BMI (P-value = 0.043) and risk for overweight and obesity [odd ratio (95% CI) = 2.621 (1.301–5.280), P  = value = 0.007] showed the subjects with poor sleep quality. Among subjects with worse eating habits after going abroad, the subjects with poor sleep quality increased their risk for overweight and obesity (OR = 3.433, 95% CI = 1.063–11.085, P  = value = 0.039) compared to subjects with good sleep quality. However, those findings were not shown the subjects with better eating habits after going abroad. Conclusions: The results of this study demonstrated that sleep quality was associated with eating habits after going abroad, and overweight and obesity among international students in South Korea. Funding Sources: This study was supported by the Basic Science Research Program of the National Research Foundation of Korea (NRF-2019R1C1C1002149) funded by the Ministry of Science.